PERANAN BKKBN DALAM PEMBANGUNAN KESEJAHTERAAN SOSIAL (Suatu Studi di Badan Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Minahasa Selatan) - KAWULUR, ANDRE; DENGO, SALMIN; ROMPAS, SONNY (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTIn accordance with the duties and functions BKKBN or Regional FamilyPlanning Agency has a strategic role in the development of social welfare . The role willbe realized as expected if the Family Planning Agency may formulate and implementprograms that are directly related to efforts to repair / improvement of social welfare inparticular the families of the target group . In connection with this, this peneleitianendak answer the question " how the role of Family Planning Agency in thedevelopment of social welfare in the South Minahasa district .What is meant by a role in the development of the social welfare are the thingsor the efforts that have been or are being carried out by the Family Planning in thedevelopment of social welfare / community in accordance with the scope of tasks andauthority. The role can be seen from the programs and activities that have been or arebeing implemented and the results achieved in the development of public welfare .This study used qualitative methods . Sources of data / informants drawn fromthe competent authorities Family Agency Planning South Minahasa District ( 5 people ), officers PPLKB / PLKB Subdistrict ( 4 ) people , and community family planningprograms target group ( 6 persons ) , so the total number of informants there are asmany as 15 people . Collecting data using interview techniques . While the analysis ofthe data using qualitative analysis techniques interactive model of Miles and Hubernan .The results showed : ( 1 ) Programmes Body Family Planning , Women'sEmpowerment and Child Protection South Minahasa regency set everything can be donequite effectively . ( 2 ) Programs Board of Family Planning , Women's Empowermentand Child Protection South Minahasa District conducted during this provide greatbenefits for the community , especially the target groups in the welfare of the family.Based on the results of these peneleitian be concluded that the FamilyPlanning Agency has a significant role in realizing the social welfare development inSouth Minahasa regency .Starting from the conclusion it is suggested that given the significant role ofBKKBN or Regional Family Planning Agency in the development of the social welfareprograms of the Agency for Family Planning , Women's Empowerment and ChildProtection South Minahasa District that has been or is being implemented today shouldbe continued , improved and expanded even furtherKeywords : role KB Agency , the development of social welfare .